Muscular and functional capacity in subjects under treatment for knee osteoarthritis: Role of physical activity status - Da Silva, José Messias Rodrigues [UNESP]; De Rezende, Marcia Uchoa; Spada, Tânia Carvalho; Da Silva Francisco, Lucila; Dos Santos, Helenilson Pereira; De Andrade Souza, Robson; D'Andréa Greve, Júlia Maria; Ciolac, Emmanuel Gomes [UNESP] (Human Kinetics, 2019)
Background: The purpose of this study was to assess the role of physical activity (PA) in muscular and functional capacity in subjects under treatment for knee osteoarthritis submitted to an interdisciplinary educational program emphasizing the regular practice of PA and exercises. Methods: Subjects under treatment for primary knee osteoarthritis (N = 136; age = 66 [3]) were allocated in sedentary to sedentary (SED−SED, sedentary or insufficiently active at pre and post), active to sedentary (ACT−SED, active or very active at pre and sedentary or insufficiently active at post), sedentary to active (SED−ACT, sedentary or insufficiently active at pre and active or very active at post), and active to active (ACT−ACT, active or very active at pre and post) groups. Muscular capacity (isokinetic test), functional capacity (timed up and down stairs test, timed up and go test, and 5 times sit to stand test), and daily living PA (International PA Questionnaire short version) were assessed before and after (12 mo) the follow-up. Results: There were improvements in performance (P < .05) in the time to up and down stairs: 37% in SED-ACT and 27.5% in ACT-ACT; timed up and go test: 33.5% in SED-ACT, 19% in ACT−SED, and 40% in ACT-ACT; 5 times sit to stand test: 39% in SED-ACT and 51% in ACT-ACT groups after 12 months of follow-up. Conclusions: The present results suggest that high levels of daily living PA may have an important role in the prevention/management of knee osteoarthritis.
Keywords: Daily living physical activity; Educational program; Isokinetic; Physical exercise; Physical fitness